Do Equivalence Trials Display Superiority Over the Traditional Comparative Study Methods in Orthopedic Surgery?. Issue 5 (June 2020) - Hughes, Andrew J.; Temperley, Hugo C.; Ahern, Daniel P.; McDonnell, Jake; Butler, Joseph S.
Abstract : Superiority and equivalence trials are 2 commonly encountered methods of designing randomized controlled trials. Traditionally, the goal of a randomized controlled trial is to show superiority. However, in more recent times, there has been a tendency to show equivalence in clinical randomized trials. These differing conclusions at first glance seem to be drawn on the basis of the results of the respective trials. However, to accurately reach these conclusions, there are stark contrasts in the methodologies of these different study types. This article provides a brief overview of superiority and equivalence trials, highlights the differences between the 2, and their relevance to orthopedic surgery.